Inducing-Yang-to-Yin tuina therapy for relief of insomnia in a patient with artificial heart implantation and related nursing measures (引阳入阴失眠推拿改善1例人工心脏植入患者失眠的护理体会) - LI Chenchen (李陈晨); YANG Yu (杨宇); LI Mengru (李梦儒); TANG Ling (唐玲); HU Shirong (胡世荣) (中西医结合护理)
This paper observed the effect of Inducing-Yang-to-Yin Tuina therapy for relief of insomnia in a patient with artificial heart implantation, and summarized the experience of tuina therapy, psychological care and basic nursing. Based on the Traditional Chinese Medicine syndrome differentiation, Inducing-Yang-to-Yin tuina therapy is safe, easy to operate and effective for relief of insomnia in a patient with artificial heart implantation. (本文总结了1例应用引阳入阴失眠推拿技术改善人工心脏植入患者失眠的护理经验, 包括推拿的操作方法、心理护理以及常规护理等。引阳入阴失眠推拿具有绿色、安全、可操作性好等特点, 患者依从性高, 基于中医辨证施护, 能有效改善人工心脏植入患者失眠症状, 提高患者生活质量。)